PROSPECTS OF INNOVATIVE DEVELOPMENT OF THE AGRICULTURAL NETWORK (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
As the population grows, the demand for agricultural products increases. The introduction of innovative technologies in the sustainable development of this sector and the increase in agricultural production with the rational use of resources is becoming increasingly important. This article analyzes the current state of development of the agricultural industry, developed indicators of prospects and the main directions of innovative development.